E-Commerce Based Human Resource Management Strategies for the Development of Batik Fosil Widi Nugraha Ngawi Micro, Small, and Medium Enterprises - Lina sugiyanto; Rachmawati Koesoemaningsih; Khoyrul Anwar (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Micro, Small, and Medium Enterprises (MSMEs) based on local wisdom play a strategic role in supporting regional economic development while preserving cultural values. Batik Fosil Widi Nugraha MSME in Ngawi is a creative enterprise that adopts fossil-inspired batik motifs as its product identity; however, it still faces various challenges in business development, particularly in human resource management and the utilization of e-commerce. This study aims to analyze the development strategy of Batik Fosil Widi Nugraha MSME in Ngawi through e-commerce-based human resource management. This research employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observation, and documentation involving the business owner and employees engaged in production and marketing activities. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation techniques. The findings indicate that human resource management in Batik Fosil Widi Nugraha MSME remains informal and has not been systematically integrated with e-commerce utilization strategies. Although the use of e-commerce is still limited, it demonstrates significant potential in expanding market reach and enhancing business competitiveness. The recommended development strategies include improving employees’ digital competencies, restructuring work roles, integrating local cultural values into digital marketing, and strengthening collaboration with relevant stakeholders. This study emphasizes that e-commerce-based human resource management is a key factor in achieving sustainable development of culture-based batik MSMEs.